1988
DOI: 10.1093/ajcn/48.5.1166
|View full text |Cite
|
Sign up to set email alerts
|

Educational intervention for altering water-sanitation behavior to reduce childhood diarrhea in urban Bangladesh: impact on nutritional status

Abstract: We evaluated whether an educational intervention that was effective in reducing childhood diarrhea also improved childhood nutritional status. Fifty-one communities of 38 families each were randomized to receive the intervention or no intervention. During 1 y of follow-up the rate of diarrhea (per 100 wk) in children less than 6 y in the intervention group was 5.89 episodes whereas that in the nonintervention group was 7.55 episodes (protective efficacy 22%; p less than 0.0001). During the same follow-up perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Our findings are consistent with past observational studies that have showed that gains in height are largest with joint improvements in water and sanitation conditions 28–31. However, multiple intervention studies have documented no effect of household environmental improvements on HAZ, and the relationship between environmental improvements and growth remains ambiguous 15,32,33. Of the intervention studies to date, just one has measured the effects on markers of environmental enteropathy 15.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with past observational studies that have showed that gains in height are largest with joint improvements in water and sanitation conditions 28–31. However, multiple intervention studies have documented no effect of household environmental improvements on HAZ, and the relationship between environmental improvements and growth remains ambiguous 15,32,33. Of the intervention studies to date, just one has measured the effects on markers of environmental enteropathy 15.…”
Section: Discussionsupporting
confidence: 88%
“…We did not find evaluations conducted in rainy or dry season to demonstrate significantly different results. 24 Indeed, while one may expect greater impact of an intervention in the rainy season when water-borne diseases are more likely to flourish, this may be balanced by increased consumption of relatively clean rain water during rainy season (Tiwari et al 2009) or increased consumption of contaminated water from other sources as a result of water scarcity in the dry season (Ahmed et al 1993, Clasen et al 2004, and heavy rains may also wash away debris (Stanton et al 1988). On the contrary, interventions conducted during part of the year (either in rainy or dry season) tended to show more effective impact on diarrhoea morbidity than those conducted year-round, suggesting that, as the analysis controlled for intervention type, study length was the driving factor behind these results.…”
Section: Effectivenessmentioning
confidence: 99%
“…23. Aziz et al (1990a), Ahmed et al (1993), Bateman et al (1995), Conroy et al (1999), Chiller et al (2006), Garrett et al (2008), Haggerty et al (1994), Hoque et al (1996), Huttley et al (1990, Pattanayak et al (2007), Pinfold and Horan (1996), Pradhan and Rawlings (2002), Stanton et al (1988), Torun (1982). 24.…”
Section: Estimates Of Cost-effectiveness In Terms Of Dollars (Us$) Pementioning
confidence: 99%
“…Using aggregate data, Poskitt et al (16) showed that the secular decline in clinic attendance for diarrhoea did not come with a secular rise in mean weight and mean length at age 1 and 2 y in a Gambian population. A randomized controlled trial in urban Bangladesh successfully reduced diarrhoeal incidence but had no effect on weight gain (14). This is a longitudinal study of a Pakistani birth cohort.…”
mentioning
confidence: 99%
“…The hypothesis that diarrhoea is a causal determinant of nutritional status and growth is widely endorsed by international health organizations (12). Prevention of diarrhoea morbidity has been considered a strategy to prevent growth faltering (13,14). In a comprehensive review of the evidence, however, Briend showed that there were temporal ambiguities and inconsistencies in ndings in the empirical literature (15).…”
mentioning
confidence: 99%